ChemInform Abstract: Oxyarylation and Aminoarylation of Styrenes Using Photoredox Catalysis. Issue 4 (28th January 2014) - Fumagalli, Gabriele; Boyd, Scott; Greaney, Michael F.
Abstract The newly developed three‐component coupling of styrenes proceeds well with a low catalyst loading.